Hypoalbuminemia as a Predictor for Complications Following Coronary Artery Bypass Grafting - Masoud Seyedian; Akram Jalili; Mohammad Ali Sheikhi; Seyed Mohammad Hassan Adel (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: There is little information about the prognostic role of preoperative serum albumin levels in postoperative outcomes following coronary artery bypass grafting (CABG). The aim of this study was to evaluate preoperative hypoalbuminemia as a predictor for complications after CABG. Materials and methods: This prospective observational study was conducted in 200 patients undergoing CABG in Ahvaz Golestan Hospital, 2020. The patients were classified into two groups based on pre-operative hypoalbuminemia (serum Alb <3.5 g/dL). The association between hypoalbuminemia and clinical characteristics and outcomes including postoperative complications, ventilator duration, and length of hospital stay was assessed. Results: Preoperative hypoalbuminemia was observed in 38 (19%) patients. Patients with hypoalbuminemia had higher postoperative complications including hemorrhage, infection, cardiac arrest, AKI, and in-hospital mortality than patients with normal albumin levels (84.2% vs. 13%, P<0.0001). Ventilator duration, length of hospital stay and ICU were significantly longer in hypoalbuminemia patients than normal albumin group (P<0.0001). Preoperative hypoalbuminemia (P<0.0001), ventilator duration (P=0.025), and length of hospital stay (P=0.002) were independent predictors of CABG postoperative complications. Conclusion: Preoperative hypoalbuminemia was associated with postoperative mortality and complications, including hemorrhage, infection, stroke, and AKI development in patients undergoing CABG procedure. Thus, serum albumin measurement before CABG as a clinically implementable and easy method could be used for management and prevention of postoperative complications.